2013
DOI: 10.1080/02640414.2013.796065
|View full text |Cite
|
Sign up to set email alerts
|

Combined strength and power training in high-level amateur football during the competitive season: a randomised-controlled trial

Abstract: We aimed to analyse the effects of combined strength and power training during the competitive season on physical fitness in high-level amateur football players. Sixteen male players (22.5 (SD 2.5) years, 1.79 (0.05) m, 76.8 (6.1) kg) from one team were randomly assigned to either a strength training (ST, N = 8) or a control (CON, N = 8) group. ST conducted lower extremity resistance exercises combined with plyometrics and/or sprints 2 × 30 min per week for 7 weeks. CON performed technical-tactical training du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 25 publications
8
74
1
2
Order By: Relevance
“…In the present study, the magnitude or relative improvement was similar to that previously reported for analogous slow stretch-shortening cycle (i.e., countermovement and countermovement with arms jumps) (Faude, Roth, Di Giovine, Zahner, & Donath, 2013) and fast stretch-shortening cycle (i.e., 40 cm drop jump) muscle actions (Faude et al, 2013;Michailidis et al, 2013) after plyometric training with male and female soccer players using interventions of similar duration or number of sessions. These Table III changes might have a positive effect on the percentage of games won (Faude et al, 2013) and could have been induced by neuromuscular adaptations (Markovic & Mikulic, 2010). The plyometric training groups showed a similar increase in medicine ball throwing performance, which was greater compared to control groups (Tables II and III).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the magnitude or relative improvement was similar to that previously reported for analogous slow stretch-shortening cycle (i.e., countermovement and countermovement with arms jumps) (Faude, Roth, Di Giovine, Zahner, & Donath, 2013) and fast stretch-shortening cycle (i.e., 40 cm drop jump) muscle actions (Faude et al, 2013;Michailidis et al, 2013) after plyometric training with male and female soccer players using interventions of similar duration or number of sessions. These Table III changes might have a positive effect on the percentage of games won (Faude et al, 2013) and could have been induced by neuromuscular adaptations (Markovic & Mikulic, 2010). The plyometric training groups showed a similar increase in medicine ball throwing performance, which was greater compared to control groups (Tables II and III).…”
Section: Discussionsupporting
confidence: 83%
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
“…In fact, the qualitative adaptations that accompany the player's maturation are important for correlations between players' speed and age (Mendez-Villanueva et al, 2011). Faude et al (2013) argued that the maturational process was a significant moderator variable that modifies the effect of the strength training during the critical period of maturation between 18 to 22 years of age (i.e., a period of years close to the sample used in the present study). Thus, the age, biological maturity or years of training affect the players' physical and physiological profiles such as speed or sprinting (Lago-Peñas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a 6-week resistance training program combined with plyometrics plus a soccer training program induced gains for both 20 m performance and CMJ (Franco-Márquez et al, 2015). Faude et al (2013) identified that strength trained in combination with sprinting exercises resulted in greater adaptations in sprint speed as compared with strength training alone in high-level amateur soccer players. In another study on the effect of a plyometrics training program, including half-squat and leg-curl exercises, the experimental group improved both 20 m performance and CMJ (De Hoyo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation